Integration of High Velocity Elastic Band for Hamstring Training in Pre-Season Routine of Football Players (Baltic Journal of Sport and Health Sciences, 2020)
Background. A need for other methods of hamstring strengthening are thus warranted with the main aim of reducing the risk of injury during the subsequent intense athletic activities. The study aimed to examine changes in hamstring strength in response to high velocity elastic band training when incorporated into regular training routine of football players.Methods. Research participants were professional top level football players (age 23.1 ± 5.7 years; weight 77.2 ± 7.7 kg, training experience 14.1 ± 5.8 years). In the pre-season, in addition to their routine training, the experimental group performed hamstring curls at maximal intensity while lying prone three times per week for five weeks, while control group continued their routine training. Concentric knee torque at 60°/s and 180°/s angular velocities, countermovement jump height, 30m sprint running performance from standing and flying start, and knee flexion-extension movement frequency were measured before and after the 5 weeks of training.Results. Hamstring curl frequency during lying prone increase by 10.5 % (p < .05) in the experimental group and did not change in the control group. Peak torque for knee flexion and knee extension, jump height and sprint running performance did not change significantly in any group (p > .05).Conclusion. High velocity elastic band training incorporated into regular pre-season routine is beneficial for football players to increase their knee extension-flexion maximal movement frequency with no evident effects on strength, jump and sprint running performance. Results might be related with concurrent training during preparatory training phase of the pre-season when several physical capacities are being developed simultaneously.Keywords: high speed movements; peak torque; sprint performance; prevention of hamstring injuries; knee flexion strength.